Pengaruh Faktor Internal dan Eksternal Terhadap Profitabilitas Bank Syariah di Indonesia - Firda Hanifa; Ani Silvia; Nendi Juhendi (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
This study aims to determine the effect of Internal Factor and External Factor on Profitability on Profitability in Islamic Banking listed in Indonesia Central Bank and Financial Service Authority (OJK) . In this study, the explanatory method is used to explain the influence between the independent variables namely Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Inflation, and Exchange Rate on the dependent variable, namely Retiurn on Asset (ROA) and explain the relationship between variables. The population in this study is islamic banking listed on the Indonesia Central Bank and Financial Service Authority for the period 2013-2017. Sample selection through purposive sampling method. There are 11 companies that meet the criteria as research samples, so the research data amount is 220 data. Data collection techniques carried out were document review, data reviewed were quarterly financial reports, transaction data of Indonesia Central Bank, previous research journals and other literature related to research problems. Processing and data analysis techniques include financial management analysis, multiple linear regression analysis, classic assumption test, hypothesis testing, coefficient of determination test and multiple correlation coefficient test. The results of the study show that partially CAR and Inflation variables have a positive and significant influence on ROA. Meanwhile, FDR variable have a negative and signifikan influence on ROA. This shows that the higher FDR, the smaller ROA. The other way around, the smaller FDR, the higher ROA. On the other side, Exchange Rate partially have no signifikan infuence on ROA. Meanwhile, simultaneously research results shows that CAR, FDR, Inflation, and Exchange Rate have a positive and significant effect on ROA. Keywords: Profitability, Capital Adequacy Ratio, Financing to Deposit Ratio, Inflation, Exchange Rate, Islamic Banking